2013
DOI: 10.1161/circulationaha.112.000841
|View full text |Cite|
|
Sign up to set email alerts
|

Duration of Ventilations During Cardiopulmonary Resuscitation by Lay Rescuers and First Responders

Abstract: In the Netherlands, when a cardiac arrest is suspected, 2 ambulances equipped with a manual defibrillator are sent by the dispatcher. Besides the ambulance, the dispatcher sends firefighters or policemen (first Background-The 2010 guidelines for cardiopulmonary resuscitation allow 5 seconds to give 2 breaths to deliver sufficient chest compressions and to keep perfusion pressure high. This study aims to determine whether the recommended short interruption for ventilations by trained lay rescuers and first resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 19 publications
2
29
0
2
Order By: Relevance
“…Moreover, our testing conditions were very challenging because pauses were very short (median duration 4.7 s). Indeed, pauses for two ventilations in CPR performed by laypersons may last around 7 s (IQR, 6-9), 28 in those circumstances the accuracy and reliability of the detector would further improve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our testing conditions were very challenging because pauses were very short (median duration 4.7 s). Indeed, pauses for two ventilations in CPR performed by laypersons may last around 7 s (IQR, 6-9), 28 in those circumstances the accuracy and reliability of the detector would further improve.…”
Section: Discussionmentioning
confidence: 99%
“…27 Basic Life Support (BLS) guidelines recommend 30:2 CV-ratio CPR. At the standard rate of 100 compressions per minute, pauses for two ventilations occur approximately every 20 s. Furthermore, in BLS scenarios these pauses normally last longer than 5 s. 28 Recently, Ruiz et al 29 proposed doing rhythm analysis during these pauses because the ECG would not have chest compression artefacts. This would allow an accurate rhythm assessment every 20 s during CPR.…”
Section: Introductionmentioning
confidence: 99%
“…79 In an investigation of first responders equipped with AEDs, the duration of pauses specific to ventilation was not associated with survival. 80 …”
Section: Summary Of Evidencementioning
confidence: 99%
“…For the critical outcome of favorable neurologic outcome, we found 1 low-quality observational study (downgraded for imprecision) 147 enrolling 199 patients. This study compared survival against a reference ventilation range of 5 to 6 seconds and found no difference with longer ranges of time for 2 breaths delivered by lay rescuers, ranging over 10 to 12 seconds (adjusted OR, 1.30; 95% CI, 0.29-5.97) and 13 seconds or greater (adjusted OR, 2.38; 95% CI, 0.46-12.1).…”
Section: Consensus On Sciencementioning
confidence: 99%